Business Continuity and Disaster Recovery in Snowflake: A Technical Deep Dive - Jaya Krishna Vemuri (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This technical deep dive examines Snowflake’s comprehensive approach to Business Continuity and Disaster Recovery (BC/DR) in cloud-based data warehousing environments. The article explores how Snowflake addresses the challenges of exponential data growth and increasing real-time processing demands through advanced features including geo-redundant storage, time travel capabilities, and automated failover mechanisms. It article the platform’s implementation of security frameworks, continuous data protection, and audit logging while providing detailed insights into best practices for organizations implementing BC/DR strategies. The discussion encompasses the technical architecture, performance optimizations, and practical considerations for maintaining operational resilience across multiple cloud providers and geographical regions, offering a comprehensive framework for enterprise-grade disaster recovery implementation.